Smoothing of the Singularities of Functions Whose Integrals over the Balls on a Sphere are Zero - Volchkov, V. V.; Savost’yanova, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We study functions defined on a sphere with prickled point whose integrals over all admissible “hemispheres” are equal to zero. A condition is established under which the point is a removable set for this class of functions. It is shown that this condition cannot be omitted or noticeably weakened.